Comparative Education Discourse in Italy After WWII: The Case of Giovanni Gozzer - Gaudio, Angelo (Rivista di Storia dell’Educazione, 2018)
Presentation of the writings of comparative education of Giovanni Gozzer, authoritative protagonist of the pedagogic debate and adviser of many ministers of the public education in the second postwar period. He tried to introduce in Italy the international public discourse on the bonds between education and economy. Its activities were developed before in the circle of the Unione Cattolica Italiana Insegnanti Medi (UCIIM) and then in the direction of the Centro Europeo dell’educazione in Frascati.